Absence of Gut Microbiota Reduces Emotional Reactivity in Japanese Quails (Coturnix japonica) - Kraimi, Narjis; Calandreau, Ludovic; Biesse, Manon; Rabot, Sylvie; Guitton, Edouard; Velge, Philippe; Leterrier, Christine (Frontiers in Physiology, 2018)
Objective: Recent studies have demonstrated an effect of the gut microbiota on brain development and behavior leading to the concept of the microbiota-gut-brain axis. However, its effect on behavior in birds is unknown. The aim of the present study was to determine the effect of the absence of gut microbiota on emotional reactivity in birds by comparing germ-free (GF) quails to those colonized (COL) with gut microbiota. Material and Methods: From hatching, the quails of both groups GF (n = 36) and COL (n = 36) were reared in sterile isolators. The COL quails were colonized at day 2 by introducing a pool of droppings from conventional adult females into the drinking water and feed. The quails were weighed individually on day 2, 6 and 14. From day 8, emotional reactivity was assessed in each group in the isolators through several behavioral tests. Results: GF quails showed a considerable decrease in emotional reactivity demonstrated by spending less time in tonic immobility during the tonic immobility test (242 s ± 31 vs 331 s ± 32, p ≤ 0.05), traveling a shorter distance (3897 cm ± 242 vs 4827 cm ± 278, p ≤ 0.05) at a lower velocity (6.55 cm/s ± 0.4 vs 8.1 cm/s ± 0.5, p ≤ 0.05) during the social separation test and spending more time near an object at the beginning of the novel object test (33.7 s ± 6.4 vs 18.5 s ± 4.1, p ≤ 0.05). No difference in growth was found between the 2 groups. Conclusion: For the first time, this study demonstrates that the absence of gut microbiota reduces emotional reactivity in Japanese quails in situations of fear and social perturbation without influence on growth.